Analysis of Consumer Acceptance on the Development of Gudril Crackers as a Local Product of SMEs in Cimindi Tourism Village, Pangandaran Regency - Mardaweni, Riri; Widiastuti, Raden Meina (Gema Wiralodra, 2024)
Gudril crackers are a local food product of Cimindi Tourism Village, Pangandaran Regency, produced by the MSME Good Real Pasundan. These crackers are made from cassava using a uniqe manufacturing process that involves smoothing, pressing, steaming, cutting, and drying without the use of flour. This study aimed to analyze consumer preference for gudril crackers through hedonic testing. A hedonic test was conducted with 35 panelists using a 7-point likert scale (1=strongly dislike to 7=strongly like) to assess attributes such a color, aroma, taste, texture (crispness), and overall liking. The result showed that  the orignial gudril crackers and a variant with added mackerel had the highest average score (6.0) across all atributes, indicating a strong positive response from panelists. However, some areas for improvement were identified, particularly in the mackerel variant, where the savory taste, aroma, and texture could be optimized. In general, the aroma of gudril crackers has potential for enhancement. This study provides valuable information for Good Real Pasundan to further develop gudril cracker products that are more appealing to consumers and have the potential for wider market distribution.